(3GdEOGQI GdESJQGJjLjI dJcGdja Gdfbd OhQgG aj JfejI MQcI GdJLGQI GdHjfjI (B/s - (3jhSa, eMeO eMehOs ((3GdbGgQI(B: s (3GdefXeI GdYQHjI ddJfejI GdEOGQjI(B, s, 2003)
(3fTGW Gdfbd HGdhWf GdYQHj(B- (3GdEOGQI GdESJQGJjLjI dfTGW Gdfbd ddeSJhjGJ GdKdGK (B( (3JTZjdj, Ebdjej, bhej, Ebdjej YQHj(B)- (3ebJQMGJ Mhd GdHYO GdESJQGJjLj dJMdjd JcGdja Gdfbd hJaYjd MQcI GdJLGQI GdHjFjI Hjf GdOhd GdYQHjIs
(3GdeQGLY U(B.205s
Keywords: (3GdEOGQI GdESJQGJjLjIs; (3GdJLGQI GdYQHjIs; (3GdJcGdja(B- (3Gdfbd(B- (3GdHdGO GdYQHjIs; (3GdJfXje hGdEOGQI(B- (3Gdfbd(B- (3GdHdGO GdYQHjIs